If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(3n + -3) + -1n = 0 Reorder the terms: -5(-3 + 3n) + -1n = 0 (-3 * -5 + 3n * -5) + -1n = 0 (15 + -15n) + -1n = 0 Combine like terms: -15n + -1n = -16n 15 + -16n = 0 Solving 15 + -16n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -16n = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -16n = 0 + -15 -16n = 0 + -15 Combine like terms: 0 + -15 = -15 -16n = -15 Divide each side by '-16'. n = 0.9375 Simplifying n = 0.9375
| 4(1-4v)+3v= | | 15x^2+1-[4(x^2-8)+7]=0 | | 3(5x-4)+x= | | -5x-5(4-3x)= | | -3(1-2a)+5= | | x+8=0+2 | | 5(-4v-4)-3= | | 0+8=y+2 | | -2(-3-5b)-4b= | | -3(1-2n)= | | -20x^2-52x-24=0 | | 0.4v^2+0.7v=0.3v-2 | | -(5a-2)= | | 0.9x-4.7=.07 | | -2(-4x-2)= | | -25/2-600=75x+100y | | -4(5-n)= | | -3(5m-2)= | | -2(k+2)= | | -(1-2p)= | | 3y=x+2y | | f(-1)=0 | | x-3/15+x+5/4-2x-1/9 | | 5x-6*0=38 | | -6y=38 | | 3x=-4*0 | | (7/2t)-2=4+4t | | 1+n-4= | | -3r-5r= | | 1.4x+3=0 | | -1b-4b= | | 0=3x/7x+23 |